Ultrasound-guided breast-conserving surgery compared to conventional breast-conserving surgery - Boeer, Bettina; Obermoser, Jennifer; Marx, Mario; Schönfisch, Birgitt; Grube, Marcel; Röhm, Carmen; Helms, Gisela; Fugunt, Regina; Hartkopf, Andreas D; Brucker, Sara Y; Hahn, Markus (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
The goal of breast-conserving surgery is to achieve negative tumor margins, since insufficient marginal distance is associated with more local and distant recurrences. This study investigates whether IOUS (intraoperative ultrasound) can reduce the re-resection rate compared to standard breast surgery, regardless of tumor biology and focality.The present study is a monocentric, prospective, randomized, and non-blinded parallel group study conducted between 7/2015 and 2/2018. Patients with sonographically visible breast cancer were randomized into two study arms: 1) breast-conserving surgery with IOUS; 2) conventional arm.364 patients were included in the study and underwent surgery. Tumor biology, size, and focality were equally distributed in both groups (p = 0.497). The study arms did not differ significantly in the proportion of preoperative wire markings (p= 0.084), specimen weight (p = 0.225), surgery duration (p = 0.849), and the proportion of shavings taken intraoperatively (p = 0.903). Positive margins were present in 16.6% of the cases in the IOUS arm and in 20.8% in the conventional arm (p = 0.347). Re-operation was necessary after intraoperative shavings in 14.4% of cases in the US arm and in 21.3% in the conventional arm (p = 0.100).Although the present study showed a clear difference in the rate of positive tumor margins with IOUS compared to conventional breast surgery without IOUS, this was not statistically significant in contrast to the current literature. This could be due to the high expertise of the breast surgeons, the precise wire marking, or the fact that the IOUS technique was not standardized.
Keywords: intraoperative ultrasound; resection margins; breast-conserving surgery; breast cancer